GAMBARAN SEL DARAH MERAH SAPI BALI (STUDI RUMAH POTONG) - -, Siswanto (Buletin Veteriner Udayana, 2012)
A study to observed the profile of erythrocytes of bali cattle was conducted from 2000 to2007 years at Veterinary Physiology Laboratory, Faculty of Veterinary Medicine, UdayanaUniversity. The aim of this observation were to study and evaluated erythrocytes andcomplete the data. A total of samples is one hundred ninety-two blood samples were takenfrom bali cattle were slaughtered at the abattoir of Sanggaran Denpasar. The parametersobserved were the number erythrocytes (Hemocytometer Method), hemoglobineconsentration,(Sahli method) PCV, MCV (fl), MCH (pg), and MCHC (%/dl) usingMicrohematocrite method. Results of this observation showed that there ware totalerythrocytes 5,2 million/mm3, hemoglobine consentration 8,7 gr%, PCV 27,2 %, MCV56.2 fl, MCH 16.7 pg, and MCHC 29.8 %/dl.
Keywords: erythrocytes, hemoglobine, PCV, MCV,MCH,MCHC , bali cattle.